The experience and needs of informal caregivers of people with dementia in rural Vietnam: a qualitative study - Tuan-Anh Tran; Siti Maisarah Mattap; Narelle Warren; Jananie Chandrarao; Duc Minh Duong; Minh Van Hoang; Shajahan Yasin; Devi Mohan (Annals of Medicine)
Objectives Caregivers of people with dementia living in rural areas face numerous challenges owing to the progressive nature of the disease, limited resources, and inadequate support services. Research on how caregivers experience dementia caregiving in Vietnam and similar Asian settings is limited. This study explored caregivers’ experiences, consequences, and caregiving needs in a rural district of Hanoi.Methods We recruited 20 dyads (people with dementia and their caregivers) and eight health professionals. A qualitative study design using a semi-structured interview approach was employed. This study used a thematic analysis approach.Results Nine major themes were identified: (1) stepping into the caregiver role and responsibilities; (2) supporting activities of daily living; (3) managing behavioural problems; (4) complex care needs; (5) caregiver-related challenges; 6) healthcare-related challenges; (7) knowledge, perception, and awareness of caregivers; (8) consequences of caregiving; and (9) perceived needs.Conclusion Thematic analyses revealed that the caregiving challenges of dementia caregivers were related to behavioral disturbance, functional care needs, complex care needs, caregiver-related challenges, healthcare-related challenges, understanding of dementia, and stepping into the caregiver role and responsibilities. The consequences of caregiving affect caregivers’ physical, psychological, and financial health. Understanding their experiences is essential for developing effective interventions to reduce caregiving burden and improve the quality of care.